Effect of different irradiance levels on bioelectricity generation from algal biophotovoltaic (BPV) devices - Thong, Cheng Han; Phang, Siew Moi; Ng, Fong Lee; Periasamy, Vengadesh; Ling, Tau Chuan; Yunus, Kamran; Fisher, Adrian C. (Wiley Open Access, 2019)
Rapid population and economic growth in the world have accelerated the search for new sustainable and environment-friendly energy sources. Power-producing systems generally add to the carbon load in the environment, contributing to global climate change. In photosynthesis, energy from light splits water molecules into oxygen, protons, and electrons. Algal biophotovoltaic (BPV) platforms were developed to harvest these electrons to generate bioelectricity through algal photosynthesis. Irradiance is one of the most important parameters that determine power output efficiency from algal BPV devices. In this study, the effective range of irradiance levels for power generation from algal BPV devices comprising of suspension and alginate-immobilized Chlorella cultures on ITO anodes was determined. Immobilized cultures were prepared by entrapping the algal cells in 2% sodium alginate solution. The algal BPV devices were illuminated by four different irradiance levels (30, 90, 150, and 210 µmol photons m−2 s−1). The maximum power density of 0.456 mW m−2 was generated from the prototype algal fuel cell at the irradiance level of 150 µmol photons m−2 s−1. At 210 µmol photons m−2 s−1, low power density was produced due to photoinhibition as indicated by Fv/Fm values generated through PAM fluorometry. In terms of carbon fixation rate, the highest value was recorded in immobilized culture at 217.11 mg CO2 L−1 d−1. The algal biophotovoltaic device is multifunctional and can provide sustainable energy with simultaneous carbon dioxide removal. © 2019 University of Malaya. Energy Science & Engineering published by Society of Chemical Industry and John Wiley & Sons Ltd.